2018
DOI: 10.1016/j.taap.2018.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Antimetastatic effect of the pharmacological inhibition of serine/arginine-rich protein kinases (SRPK) in murine melanoma

Abstract: The Serine/arginine-rich protein kinases (SRPK) are involved in pre-mRNA splicing control through the phosphorylation of the SR protein family of splicing factors. Over the last years, several studies have shown the relevance of SRPK for human cancers and their potential as promising drug targets. In this context, we have previously selected three trifluoromethyl arylamides (named here as SRVIC24, SRVIC30 and SRVIC36) with improved in vitro antileukemia effect and ability of impairing the cellular activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
0
14
0
7
Order By: Relevance
“…Yet, while these substoichiometric levels of phosphorylation are of low importance in vitro , they may be functionally significant in the cellular context, allowing a well-defined number of SRPK1 molecules to enter the nucleus. Partial nuclear translocation of SRPK1 was also observed in EGF-treated melanoma cells ( Moreira et al, 2018 ). Both nuclear and cytoplasmic staining of SRPK2 were obtained in EGF-treated HEK293T cells or cells transfected with activated Akt, whereas an antibody against p-SRPK2 stained only the nuclei of certain cells, implying that a fraction of the kinase was phosphorylated and entered the nucleus ( Jang et al, 2009 Supplementary data; Zhou et al, 2012 ).…”
Section: Functional Significance Of Srpk1/2 Nuclear Translocationmentioning
confidence: 92%
See 1 more Smart Citation
“…Yet, while these substoichiometric levels of phosphorylation are of low importance in vitro , they may be functionally significant in the cellular context, allowing a well-defined number of SRPK1 molecules to enter the nucleus. Partial nuclear translocation of SRPK1 was also observed in EGF-treated melanoma cells ( Moreira et al, 2018 ). Both nuclear and cytoplasmic staining of SRPK2 were obtained in EGF-treated HEK293T cells or cells transfected with activated Akt, whereas an antibody against p-SRPK2 stained only the nuclei of certain cells, implying that a fraction of the kinase was phosphorylated and entered the nucleus ( Jang et al, 2009 Supplementary data; Zhou et al, 2012 ).…”
Section: Functional Significance Of Srpk1/2 Nuclear Translocationmentioning
confidence: 92%
“…Kinase activity is a prerequisite for the nuclear translocation of SRPKs. Blocking SRPK activity either by inactivating mutations or by the selective SRPK1/2 inhibitor, SRPIN340, efficiently impeded the entry of the kinases into the nucleus ( Ding et al, 2006 ; Jang et al, 2009 ; Zhou et al, 2012 ; Koutroumani et al, 2017 ; Moreira et al, 2018 ; Sigala et al, 2021a ).…”
Section: Signals and Post-translational Modifications That Modulate T...mentioning
confidence: 99%
“…Three studies were identified, which explored the relationship between SRPK1 and melanoma [14,79,80]. Gammons et alfound SRPK1 expression to be elevated in both uveal and cutaneous melanoma cell lines.…”
Section: Skin (Melanoma and Basal Cell Carcinoma (Bcc))mentioning
confidence: 99%
“…However, silencing was not found to impact tumour growth in vitro [79]. Moreira et al, found pharmacological inhibition of SRPK1 to inhibit migration and invasion of melanoma cells in vitro, and metastasis in vivo [80].…”
Section: Skin (Melanoma and Basal Cell Carcinoma (Bcc))mentioning
confidence: 99%
“…The SRPK1/SRSF1 axis interacts with WT-1 and regulates VEGF splicing [60] ↓SRPK1 suppressed migration, invasion, adhesion, and colony formation in vitro, also metastasis in vivo [73] SRPK1, serine-arginine protein kinase 1; NSCLC, non-small cell lung carcinoma; CSCs, cancer stem cells; TCF, T-cell factor; GSK3-β, glycogen synthase kinase 3-β; VEGF-A, vascular endothelial growth factor-A; BLBC, basal-like breast cancer; SRSF1, Serine/arginine-rich splicing factor 1; WT- In NSCLC, a main oncogenic process affected by SRPK1 was reported to be the acquisition of a CSC (cancer stem cell) phenotype. SRPK1 upregulation promoted cell growth, CSCs accumulation, and the expression of various stem cell markers, while its downregulation suppressed cell growth, CSCs, and tumorigenicity [29].…”
Section: Srpk1-mediated Mechanism(s)/ Pathway(s) Involved Referencementioning
confidence: 99%